The Instructional Learning Resources and Provision of Quality Education in public ECDE Centres in West Pokot County - Chepkonga, Mildred (IJRDO- Journal of Educational Research, 2020)
Teaching and learning materials are crucial to any successful teaching and learning process worldwide. This paper looks at how learning resources availability influence quality education provision in public pre-school centres. The paper was guided by constructivism theory which proposes that for quality learning to be achieved, the learning environment in classroom should be conducive for pupils hence provision of adequate instructional resources. The methodology for this study involved use of qualitative and quantitative approaches. The target population involved 365 head teachers, 682 teachers and 4 curriculum support officers. A sample of 37 head teachers, 205 pre-school teachers and 4 sub county programme officers for ECDE. The instruments used to collect data consisted of questionnaire, interview guide and observation checklist. Analysis of data collected was done through descriptive and inferential statistics for quantitative data while thematic content analysis was used to analyse qualitative data. The study found out that quality instructional materials in public ECDE centres in the study area were found to be inadequate. This made it impossible to use by all learners in classroom teaching.  Teaching aids, teacher guides and manuals, newspaper cuttings and pictures were found to be rarely used in ECDE centres by teachers. Textbooks, musical instruments and story books were found to be sometimes used in provision of quality education in public ECDE centres in West Pokot County. Lack of adequate and modern instructional learning resources was found to be a significant impediment to provision of quality education in public ECDE centres. The research recommended that county government needs to increase supply of instructional resources in public pre-school centres to ensure provision of quality education